The Effect of Financial Microeconomics and Macroeconomics Factors on the Sustainable Growth of the Listed Egyptian Firms - Youssef, Amr; Etab, Menan; Amer, Mrwan (The Arab Journal of Administration, 2025)
In the world of business, measuring a company’s performance is crucial to determine its success. The concept of financial sustainability has become a critical factor for companies aiming to achieve long-term success. The crucial factor in determining a company’s financial sustainability is its sustainable growth rate (SGR). In the context of frequent financial crises and the COVID-19 pandemic, the study of factors that may influence firms’ sustainable growth rate has become excessively pressing. This research investigated the effect of internal financial decisions, especially investment, financing, dividends, and working capital management along with the impact of macroeconomic factors, especially GDP growth rate, inflation, and interest rate, on firms’ sustainable growth rate. The study was conducted on a sample of non-financial firms in the EGX30 index. The study covered the period from 2009 to 2021, which provides an extensive timeline for analysis. This study is crucial for decision makers, policymakers, investors, and stakeholders as it provides valuable insights into the factors that determine the long-term growth and success of non-financial Egyptian listed firms. This research depended on the quantitative research method. Testing the research hypotheses involved regression models. The results indicated that financial leverage, dividends policy, and working capital management showed a significant negative effect, whereas the other variables demonstrated insignificant effects on the sustainable growth rate of the sample under the study. The results suggest that the impact of internal financial decisions and macroeconomic factors on the sustainable growth must be used with care as the effect may differ depending on other contexts and industries. Overall, the results highlight the complexity and variability of factors influencing sustainable growth in different sectors, emphasizing the need for careful consideration and tailored approaches when assessing and promoting sustainable growth across different sectors of business in Egypt. These results suggest that there are additional variables and factors that should be considered when investigating sustainable growth in Egypt, such as firms’ profitability, governance, firms’ ability to adapt to economic changes, and ownership structure.